A cross-sectional study of trauma certification and hospital referral region diversity: A system theory approach. Issue 3 (March 2021) - Hamadi, Hanadi Y.; Zakari, Nazik M.A.; Tafili, Aurora; Apatu, Emma; Spaulding, Aaron
Highlights: Trauma care outcome disparities do exist in diverse U.S. communities. Presence of health disparities are linked to a lower number of certified trauma centers and level I/II hospitals. Hospital referral regions with high quality performing hospitals have fewer trauma care L-I/II hospitals. As the U.S. becomes more diverse, there will be an urgent need for greater trauma care facilities in diversifying communities. Abstract: Background: There are clear racial/ethnic disparities in the trauma care service delivery. However, no study has examined the relationships between structural determinants of trauma care designations (L-I through L-IV) or verification and social factors of the surrounding health region in the U.S. Objective: This study examined the relationship between U.S. community segregation in a hospital referral region (HRR) and hospitals' attainment of trauma certification and trauma designation L-I/II. Methods: Two-year retrospective analysis of 2, 348 acute hospitals that participated in the Hospital Value-Based Purchasing (HVBP) Program. Multivariate Poisson and 1:2 matching ratio using Propensity Score Matching regressions were used. Our primary variables were composite segregation scores for each county—aggregated to the HRR level ( n =303)—and hospital performance on the HVBP Program. Results: Segregated HRRs are 69% and 40% less likely to have an increase in the number of hospitals with trauma care designations L-I/II and trauma certification, respectively. Our matching ratio showed that hospitals with trauma certification or hospitals with trauma care designations L-I/II were more likely to be within HRRs with lower community diversity. Conclusion: Our findings highlight that system disparities exist in trauma care. Research is needed to determine if other factors, such as resource allocation and reimbursement distribution, impact the availability of trauma facilities.